Impact of on-hours versus off-hours admission on outcome in pediatric patients with testicular torsion - Zlatan Zvizdic (9212371) (2024)
Objectives Testicular torsion (TT) is an emergency requiring timely surgery to prevent testicular loss. There is a lack of reports on the clinical significance of the time of admission (on-hours vs. off-hours) on the long-term surgical outcome of TT. Methods We retrospectively reviewed all consecutive patients <18 years who were admitted to the hospital and treated for TT during the ten years. Patients were classified according to their admission time: weekday (on-hours), outside working hours, and weekends (off-hours). They were also classified based on their testicular outcome: salvaged and non-salvaged testis. Results Seventy-two patients were included. Their median age was 14.2 years. Thirty-three patients (46 %) were admitted during on-hours, whereas 39 patients (54 %) were admitted during off-hours. Forty-three patients (59.7 %) required orchidopexy and, out of those, during the long-term follow-up, only 27 (37.5 %) had definitive testicular salvage. Forty-five patients (62.5 %) were with no testicular salvage. On-hours vs. off-hours admission had no impact on the clinical outcome (p= 0.25). However, significant differences in the duration of symptoms (DoS) between the orchidopexy and orchidectomy groups were observed (p < 0.001). Conclusion Testicular torsion is a time-dependent diagnosis, and any delay in treatment could cause testicular loss. Our data suggest that the DoS before admission, rather than the admission time, influences the testicular outcome. The efficient management of emergencies regardless of the time of day is a key factor for the reduced probability that admission timing affects outcomes. Other Information Published in: The American Journal of Emergency Medicine License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ajem.2024.11.024